Comprehensive management of pregnant woman with Sjögren’s syndrome - Giovanny Azalia Gunawan; Adinda Ayu Dyah Rahadina; Budi Prasetyo (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Sjögren’s syndrome is a chronic autoimmune disease that attacks the exocrine glands, especially lacrimal and salivary glands. 2. Comprehensive management of pregnant women with Sjögren’s syndrome was described.3. Clinical and laboratory examination, risk assessment and also preconception counseling before planning pregnancy are needed by women with Sjögren’s syndrome. ABSTRACT Objective: To illustrate the comprehensive management of pregnant women with Sjögren syndrome. Case Report: A 24 years old women came to Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, due to Sjögren syndrome in 35/36 weeks of gestasional age for routine examination. She was first diagnosed with Sjögren syndrome in February 2018 because she complained of dry eyes and hair fall out. This was her first pregnancy. Laboratory result showed positive ANA test. The patient had hypertension with controlled blood preasure and dry eyes. The patient was diagnosed with primigravida 35-36 weeks of pregnancy, single live intrauterine, head presentation, IUGR, screening preeclampsia was positive, and there was complication with Sjögren’s syndrome. The patient was treated by multidisciplinary team consisting of obstetricians, internists, ophthalmologists and neonatologists. Conclusion: Sjögren’s syndrome is a chronic autoimmune disease that attacks the exocrine glands, especially lacrimal and salivary glands. The exact cause of Sjögren's syndrome is still not known. Women with Sjögren’s syndrome should have clinical and laboratory examination, risk assessment and also preconception counseling before planning pregnancy because Sjögren syndrome was a rare case during pregnancy. Close monitoring and proper management was imperative to detect the early complication.